Positive electrode for lithium secondary battery, positive electrode and lithium secondary battery including the same
A multi-layered positive electrode structure with specific particle size distributions in nickel-containing lithium composite transition metal oxides addresses the cracking issue in lithium secondary batteries, enhancing rolling density and stability, and improving battery life.
Patent Information
- Application Number
- JP2023544397
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-06-28
- Filing Date
- 2022-06-09
- Publication Date
- 2025-02-03
- Estimated Expiration
- 2042-06-09
AI Technical Summary
The challenge of using nickel-containing lithium composite transition metal oxides in lithium secondary batteries is the high generation of gas and cracking of secondary particles during electrode manufacturing, leading to reduced stability and life characteristics, especially with high-nickel content, due to the bimodal distribution of secondary particles with varying average particle sizes.
A multi-layered positive electrode active material structure is introduced, comprising a first layer with larger primary particles and a second layer with smaller primary particles, each with specific average particle sizes, to enhance rolling density and prevent cracking, thereby improving the stability and life of the battery.
The multi-layered structure enhances rolling pressure, prevents short circuits, and improves the life characteristics of lithium secondary batteries by reducing cracking and maintaining capacity over cycles.
Smart Images

Figure 0007625709000003 
Figure 0007625709000004 
Figure 0007625709000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode having a multi-layered positive electrode active material layer containing a nickel-based lithium transition metal oxide, and a lithium secondary battery including the same.
[0002] This application claims priority to Korean Patent Application No. 10-2021-0084280, filed on June 28, 2021, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]
[0003] In recent years, with the rapid spread of electronic devices using batteries, such as mobile phones, notebook computers, and electric vehicles, the demand for secondary batteries that are small, lightweight, and have relatively high capacity has been rapidly increasing. In particular, lithium secondary batteries are lightweight and have high energy density, and are in the spotlight as a driving power source for portable devices. Therefore, research and development to improve the performance of lithium secondary batteries has been actively conducted.
[0004] A lithium secondary battery generates electrical energy by oxidation and reduction reactions occurring when lithium ions are inserted / deintercalated at the positive and negative electrodes, with an organic or polymer electrolyte filled between the positive and negative electrodes, which are made of active materials capable of intercalating and deintercalating lithium ions.
[0005] Lithium cobalt oxide (LiCoO2), nickel-based lithium transition metal oxide, lithium manganese oxide (LiMnO2 or LiMn2O4, etc.), lithium iron phosphate compound (LiFePO4), etc. are used as positive electrode active materials for lithium secondary batteries. Among them, lithium cobalt oxide (LiCoO2) is widely used due to its advantages of high operating voltage and excellent capacity characteristics, and is applied as a positive electrode active material for high voltage. However, due to the rising price of cobalt (Co) and unstable supply, there is a limit to its large-scale use as a power source in fields such as electric vehicles, and the development of an alternative positive electrode active material is required. In particular, a positive electrode active material made of a high-nickel-content (Ni-rich) lithium composite transition metal oxide is attracting attention in terms of its high capacity.
[0006] Currently, the commercially available nickel-containing lithium transition metal composite oxide positive electrode active material uses secondary particles formed by agglomeration of fine primary particles with an average particle size (D50) of several hundred nm. In order to increase output and rolling density, a bimodal positive electrode active material is usually used, which is a mixture of two types of secondary particles with different average particle sizes (D50), i.e., large particles made of secondary particles with a large average particle size and small particles made of secondary particles with a small average particle size.
[0007] Secondary particles formed by agglomeration of fine primary particles have a large specific surface area and low particle strength. Therefore, when an electrode is manufactured using a bimodal positive electrode active material and then rolled using a roll press, there is a problem that the secondary large particles are severely cracked, which causes a large amount of gas generation during cell operation and reduces stability. As a result, it becomes difficult to sufficiently increase the pressure of the roll press to prevent short circuits, and there is a risk of the life characteristics being reduced. In particular, in the case of high-nickel-based (high-Ni) lithium transition metal oxides in which the nickel (Ni) content is increased to ensure high capacity, if particle cracks occur due to structural problems, chemical stability is further reduced and thermal stability is also difficult to ensure. Summary of the Invention [Problem to be solved by the invention]
[0008] The problem to be solved by the present invention is to provide a positive electrode for a lithium secondary battery, which includes a positive electrode active material layer including secondary large particles and secondary small particles of a positive electrode active material having different average particle sizes, and to which a sufficiently high rolling pressure can be applied during the manufacture of the electrode.
[0009] Another problem to be solved by the present invention is to provide a positive electrode for a lithium secondary battery having improved life characteristics, the positive electrode active material layer including secondary large particles and secondary small particles of a positive electrode active material having different average particle sizes.
[0010] Another problem to be solved by the present invention is to provide a lithium secondary battery including a positive electrode for lithium secondary batteries having the above-mentioned characteristics. [Means for solving the problem]
[0011] An aspect of the present invention provides a positive electrode for a lithium secondary battery according to the following embodiment.
[0012] The first embodiment is A current collector; A first positive electrode active material layer formed on at least one surface of the current collector, a first positive electrode active material layer including at least one type of positive electrode active material particle selected from the group consisting of giant primary particles having an average particle size (D50) of 0.5 to 3 μm, secondary particles formed by aggregation of the giant primary particles and having an average particle size (D50) of 3 to 7 μm, and a mixture of these particles; A second positive electrode active material layer formed on the first positive electrode active material layer, Positive electrode active material particles formed by agglomeration of giant primary particles having an average particle size (D50) of 0.5 to 3 μm, or formed by agglomeration of fine primary particles having an average particle size (D50) smaller than that of the giant primary particles, and consisting of secondary small particles having an average particle size (D50) of 1 to 7 μm; a second positive electrode active material layer including positive electrode active material particles having an average particle size (D50) larger than that of the secondary small particles and formed by agglomeration of fine primary particles having an average particle size (D50) smaller than that of the giant primary particles, and having an average particle size (D50) of 7 to 20 μm; The positive electrode active material particles relate to a positive electrode for a lithium secondary battery, the positive electrode active material being made of a nickel-based lithium transition metal oxide.
[0013] The second embodiment is the same as the first embodiment, The present invention relates to a positive electrode for a lithium secondary battery, wherein the fine primary particles have an average particle size (D50) of 100 to 900 nm, and particularly an average particle size (D50) of 100 to 400 nm.
[0014] The third embodiment is the first or second embodiment, The present invention relates to a positive electrode for a lithium secondary battery, wherein the average crystal size of the giant primary particles contained in the first positive electrode active material layer is 200 nm or more.
[0015] The fourth embodiment is any one of the first to third embodiments, The present invention relates to a positive electrode for a lithium secondary battery, wherein the giant primary particles contained in the first positive electrode active material layer and the second positive electrode active material layer each have an average particle size (D50) of 1 to 3 μm.
[0016] The fifth embodiment is any one of the first to fourth embodiments, The present invention relates to a positive electrode for a lithium secondary battery, wherein the secondary small particles have an average particle size (D50) of 2 to 5 μm, and the secondary large particles have an average particle size (D50) of 8 to 16 μm.
[0017] The sixth embodiment is any one of the first to fifth embodiments, The positive electrode for a lithium secondary battery has an average particle size (D50) of the secondary large particles:an average particle size (D50) of the secondary small particles of 5:1 to 2:1.
[0018] The seventh embodiment is any one of the first to sixth embodiments, The content of the secondary small particles is 10 to 100 parts by weight based on 100 parts by weight of the secondary large particles.
[0019] The eighth embodiment is any one of the first to seventh embodiments, The present invention relates to a positive electrode for a lithium secondary battery, in which the thickness (a) of the second positive electrode active material layer and the thickness (b) of the first positive electrode active material layer satisfy the following mathematical formula 1: [Formula 1] 3b≦a
[0020] The ninth embodiment is any one of the first to eighth embodiments, The present invention relates to a positive electrode for a lithium secondary battery, in which the secondary small particles are composed only of secondary small particles formed by agglomeration of the fine primary particles.
[0021] The tenth embodiment is any one of the first to ninth embodiments, The nickel-based lithium transition metal oxide is Li a Ni 1-x-y Co x M 1 y M 2 w O2(1.0≦a≦1.5, 0≦x≦0.2, 0≦y≦0.2, 0≦w≦0.1, 0≦x+y≦0.2, M 1 is one or more metals selected from Mn and Al; M 2 is one or more metallic elements selected from the group consisting of Ba, Ca, Zr, Ti, Mg, Ta, Nb and Mo), and in particular Li a Ni 1-x-y Co x Mn y O2 (1.0≦a≦1.5, 0≦x≦0.2, 0≦y≦0.2, 0≦x+y≦0.2).
[0022] An eleventh embodiment provides a lithium secondary battery including the above-mentioned positive electrode. Effect of the Invention
[0023] The second positive electrode active material layer of the positive electrode according to one embodiment of the present invention has a good rolling density by including both secondary large particles and secondary small particles, and the first positive electrode active material layer interposed between the current collector and the second positive electrode active material layer includes positive electrode active material particles with low cracking tendency, so that the occurrence of a short circuit can be prevented even if a sufficiently large rolling pressure is applied during the manufacture of the electrode.
[0024] Therefore, when a positive electrode including positive electrode active material particles with improved cracking phenomenon is applied to a lithium secondary battery, the life characteristics can be improved.
[0025] The drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and serve to further understand the technical ideas of the present invention as well as the contents of the invention, and therefore the present invention should not be interpreted as being limited to the matters described in the drawings. Meanwhile, the shape, size, scale, or ratio of elements in the drawings attached to this specification may be exaggerated in order to emphasize a clearer description. [Brief description of the drawings]
[0026] [Figure 1] FIG. 1 is a schematic cross-sectional view of a positive electrode including a positive electrode active material layer having a conventional layered structure. [Diagram 2] 1 is a schematic cross-sectional view of a positive electrode having a multilayered positive electrode active material layer according to the present invention. [Diagram 3] 4 is a graph showing capacity retention rates and resistances of lithium secondary batteries according to examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Hereinafter, the embodiment of the present invention will be described in detail. Prior to this, the terms and words used in the present specification and claims should not be interpreted as being limited to their ordinary and dictionary meanings, but should be interpreted as being in accordance with the meaning and concept of the technical idea of the present invention, in accordance with the principle that the inventor himself can appropriately define the concept of the term in order to best describe the invention. Therefore, it should be understood that the configurations shown in the embodiments described in this specification are merely the most preferred embodiment of the present invention, and do not represent the entire technical idea of the present invention, and therefore there may be various equivalents and modifications that can be substituted for them at the time of this application.
[0028] Throughout this specification, when a part "includes" or "comprises" another element, it means that the part may further include the other element, not excluding the other element, unless otherwise specified.
[0029] In the present specification and claims, "comprising a large number of crystal grains" means a crystal consisting of two or more crystal grains having an average crystal size in a specific range. In this case, the crystal size of the crystal grains can be quantitatively analyzed using X-ray diffraction analysis (XRD) using CuKα X-rays (Xrα). Specifically, the average crystal size of the crystal grains can be quantitatively analyzed by placing the produced particles in a holder and analyzing the diffraction pattern produced by irradiating the particles with X-rays.
[0030] In the present specification and claims, D50 may be defined as a particle diameter at 50% of the particle size distribution, and may be measured using a laser diffraction method. For example, the average particle diameter (D50) of the positive electrode active material may be measured by dispersing the particles of the positive electrode active material in a dispersion medium, introducing the particles into a commercially available laser diffraction particle size measuring device (e.g., MT3000 manufactured by Microtrac), irradiating the particles with ultrasonic waves of about 28 kHz at an output of 60 W, and then calculating the average particle diameter (D50) corresponding to 50% of the cumulative volume in the measuring device.
[0031] In the present invention, the term "primary particles" refers to particles that have no apparent grain boundaries when observed at a magnification of 5,000 to 20,000 using a scanning electron microscope.
[0032] In the present invention, the "secondary particles" refer to particles formed by agglomeration of the primary particles.
[0033] In the present invention, the term "single particle" refers to a particle that exists independently of the secondary particles and has no apparent grain boundaries, for example, a particle having a particle size of 0.5 μm or more.
[0034] In the present invention, the term "particle" may mean any one or all of a single particle, a secondary particle, and a primary particle.
[0035] According to one aspect of the present invention, A current collector; A first positive electrode active material layer formed on at least one surface of the current collector, a first positive electrode active material layer including at least one type of positive electrode active material particle selected from the group consisting of giant primary particles having an average particle size (D50) of 0.5 to 3 μm, secondary particles formed by aggregation of the giant primary particles and having an average particle size (D50) of 3 to 7 μm, and a mixture of these particles; A second positive electrode active material layer formed on the first positive electrode active material layer, Positive electrode active material particles formed by agglomeration of giant primary particles having an average particle size (D50) of 0.5 to 3 μm, or formed by agglomeration of fine primary particles having an average particle size (D50) smaller than that of the giant primary particles, and consisting of secondary small particles having an average particle size (D50) of 1 to 7 μm; a second positive electrode active material layer including positive electrode active material particles having an average particle size (D50) larger than that of the secondary small particles and formed by agglomeration of fine primary particles having an average particle size (D50) smaller than that of the giant primary particles, and having an average particle size (D50) of 7 to 20 μm; The positive electrode active material particles provide a positive electrode for a lithium secondary battery, which is a positive electrode active material made of a nickel-based lithium transition metal oxide.
[0036] <Structure of the positive electrode active material layer> FIG. 1 is a schematic cross-sectional view of a positive electrode including a positive electrode active material layer having a conventional layered structure.
[0037] Referring to FIG. 1, in the past, a bimodal positive electrode active material, which is a mixture of large particles made of secondary particles formed by agglomeration of fine primary particles and small particles made of secondary particles formed by agglomeration of fine primary particles, was applied to at least one surface of a current collector 1 to form a single layer of positive electrode active material layer 3, thereby manufacturing a positive electrode 10.
[0038] Meanwhile, as shown in FIG. 2, the positive electrode 20 of the present invention has a multi-layered positive electrode active material layer structure in which a first positive electrode active material layer 15 containing positive electrode active material particles having predetermined characteristics is first formed on at least one surface of a current collector 11, and then a bimodal positive electrode active material is applied thereon to form a second positive electrode active material layer 17.
[0039] It is preferable that the thickness (a) of the second positive electrode active material layer satisfies the following formula 1 with respect to the thickness (b) of the first positive electrode active material layer, in consideration of the output characteristics and the intended effects of the present invention. [Formula 1] 3b≦a
[0040] <Current collector> The current collector, i.e., the positive electrode current collector, is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. may be used. The positive electrode current collector may usually have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the positive electrode current collector to increase the adhesive force of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0041] <First positive electrode active material layer> The positive electrode active material particles contained in the first positive electrode active material layer include at least one type of positive electrode active material particles selected from the group consisting of giant primary particles having an average particle size (D50) of 0.5 to 3 μm, secondary particles having an average particle size (D50) of 3 to 7 μm formed by agglomeration of the giant primary particles, and a mixture of these particles. That is, as the positive electrode active material contained in the first positive electrode active material layer, the giant primary particles having an average particle size (D50) of 0.5 to 3 μm alone, the secondary particles having an average particle size (D50) of 3 to 7 μm formed by agglomeration of the giant primary particles alone, or the giant primary particles and secondary particles mixed together may be used. In particular, the secondary particles having an average particle size (D50) of 3 to 7 μm formed by agglomeration of the giant primary particles may be used alone.
[0042] The large primary particles are nickel-based lithium transition metal oxides, specifically Li a Ni 1-x-y Co x M 1 y M 2 w O2(1.0≦a≦1.5, 0≦x≦0.2, 0≦y≦0.2, 0≦w≦0.1, 0≦x+y≦0.2, M 1 is one or more metals selected from Mn and Al; M 2 is one or more metallic elements selected from the group consisting of Ba, Ca, Zr, Ti, Mg, Ta, Nb and Mo), and in particular Li a Ni 1-x-y Co x Mn y The positive electrode active material is represented by the formula O2 (1.0≦a≦1.5, 0≦x≦0.2, 0≦y≦0.2, 0≦x+y≦0.2).
[0043] In the positive electrode active material particles contained in the first positive electrode active material layer, the large primary particles may have an average particle size (D50) of 1 to 3 μm, and the secondary particles formed by aggregation of the large primary particles may have an average particle size (D50) of 2 to 5 μm.
[0044] The giant primary particles have a larger average particle size than the conventional micro primary particles described below.
[0045] From the viewpoint of cracks, it is advantageous to have a large average particle size without any grain boundaries in appearance, like conventional single particles. If only the average particle size (D50) of the primary particles is increased by over-firing, a rock salt structure is formed on the surface of the primary particles, resulting in high initial resistance. If the crystal size of the primary particles is also grown, the resistance can be reduced. Thus, the giant primary particles according to the present invention are particles that have not only a large average particle size, but also preferably a large average crystal size, and have no grain boundaries in appearance.
[0046] When the average particle size and average crystal size of the primary particles grow simultaneously in this manner, the resistance is lowered and it has the advantage of a longer life, compared to conventional single particles, which have a large increase in resistance due to a rock salt structure formed on the surface when fired at high temperatures.
[0047] As described above, compared to conventional single particles, the "giant primary particles" used in one embodiment of the present invention, or small particles composed of aggregates thereof, or mixtures thereof, have the advantage of lowering resistance due to an increase in the size of the primary particles themselves and a decrease in the rock salt structure.
[0048] In this case, the average crystal size of the giant primary particles can be quantitatively analyzed using X-ray diffraction analysis (XRD) using CuKα X-rays. Specifically, the produced particles are placed in a holder, and the average crystal size of the giant primary particles can be quantitatively analyzed by analyzing the diffraction pattern produced by irradiating the particles with X-rays. The average crystal size of the giant primary particles can be 200 nm or more, specifically 250 nm or more, and more specifically 300 nm or more.
[0049] The first positive electrode active material layer made of such positive electrode active material particles is less prone to cracking than secondary large particles formed by agglomeration of fine primary particles, so that short circuits do not occur even if a sufficiently large rolling pressure is applied during electrode manufacturing. In addition, the cracking phenomenon of the secondary large particles is mitigated, improving the life characteristics.
[0050] <Second positive electrode active material layer> The positive electrode active material particles contained in the second positive electrode active material layer include positive electrode active material particles of secondary small particles having an average particle size (D50) of 1 to 7 μm formed by agglomerating giant primary particles having an average particle size (D50) of 0.5 to 3 μm or formed by agglomerating fine primary particles having an average particle size (D50) smaller than that of the giant primary particles, and positive electrode active material particles of secondary large particles having an average particle size (D50) of 7 to 20 μm formed by agglomerating fine primary particles having an average particle size (D50) larger than that of the secondary small particles and smaller than that of the giant primary particles.
[0051] Among the components constituting the secondary small particles, the secondary small particles formed by agglomerating the large primary particles having an average particle size (D50) of 0.5 to 3 μm are as described in the first positive electrode active material layer. Meanwhile, among the components constituting the secondary small particles, the secondary small particles formed by agglomerating the fine primary particles are secondary small particles of a bimodal positive electrode active material, and are secondary small particles commonly used in the past. The average particle size (D50) of the fine primary particles may be specifically 100 to 900 nm, and particularly 100 to 400 nm. In particular, the secondary small particles may consist only of secondary small particles formed by agglomerating the fine primary particles. The content of the secondary small particles may be 10 to 100 parts by weight based on 100 parts by weight of the secondary large particles described later.
[0052] On the other hand, the secondary large particles are positive electrode active material particles formed by agglomeration of fine primary particles having an average particle size (D50) smaller than that of the large primary particles. The fine primary particles are nickel-based lithium transition metal oxides, specifically Li a Ni 1-x-y Co x M 1 y M 2 w O2(1.0≦a≦1.5, 0≦x≦0.2, 0≦y≦0.2, 0≦w≦0.1, 0≦x+y≦0.2, M 1 is one or more metals selected from Mn and Al; M 2 is one or more metallic elements selected from the group consisting of Ba, Ca, Zr, Ti, Mg, Ta, Nb and Mo), and in particular Li aNi 1-x-y Co x Mn y The positive electrode active material is represented by the formula O2 (1.0≦a≦1.5, 0≦x≦0.2, 0≦y≦0.2, 0≦x+y≦0.2).
[0053] The secondary large particles have a larger average particle size (D50) than the secondary small particles, and specifically, the average particle size (D50) of the secondary large particles:the average particle size (D50) of the secondary small particles may be 5:1 to 2:1. The average particle size (D50) of the secondary large particles is 7 to 20 μm, more specifically, 8 to 16 μm.
[0054] Large particles having such a size are generally used as large particles for bimodal positive electrode active materials, and are produced by a typical production method described below.
[0055] As described above, the large particles formed by agglomeration of fine primary particles have a large specific surface area and low particle strength, and therefore, when an electrode is manufactured using a positive electrode active material layer in which small particles having an average particle size smaller than that of the large particles are mixed, the large particles are likely to crack due to the pressure of the roll press, making it difficult to sufficiently increase the pressure during rolling.
[0056] The present inventors solved this problem by forming the above-mentioned first positive electrode active material layer first, and then forming a bimodal second positive electrode active material layer.
[0057] <Composition of the first positive electrode active material layer and the second positive electrode active material layer> Of course, the first and second positive electrode active material layers according to the present invention may further include positive electrode active material particles having different average particle sizes or different components, in addition to the positive electrode active material particles having the above-mentioned characteristics, within the limits not impeding the object of the present invention.
[0058] The first positive electrode active material layer and the second positive electrode active material layer contain a commonly used conductive material.
[0059] The conductive material is used to impart conductivity to the positive electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery that is constructed and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one of these may be used alone or a mixture of two or more of them may be used. The conductive material may usually be contained in an amount of 1 to 30% by weight, respectively, based on the total weight of the first positive electrode active material layer and the second positive electrode active material layer.
[0060] Meanwhile, the first positive electrode active material layer and the second positive electrode active material layer may contain a binder.
[0061] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination, but are not limited thereto. The binder may be included in an amount of, for example, 1 to 30% by weight, based on the total weight of the first positive electrode active material layer and the second positive electrode active material layer.
[0062] <Manufacturing method of positive electrode> First, a method for producing positive electrode active material particles will be described with reference to an example.
[0063] The secondary particles consisting of aggregates of large primary particles according to one embodiment of the present invention may be produced by the following method, but is not limited thereto.
[0064] Nickel-based lithium transition metal oxide Li a Ni 1-x-y Co x Mn y M 2 w O2(1.0≦a≦1.5, 0≦x≦0.2, 0≦y≦0.2, 0≦w≦0.1, 0≦x+y≦0.2, M 2 A method for producing a positive electrode active material made of a compound represented by the formula (I is one or more metallic elements selected from the group consisting of Ba, Ca, Zr, Ti, Mg, Ta, Nb, and Mo) will be described.
[0065] Nickel, cobalt, manganese and M 2 A transition metal-containing solution containing the above in a predetermined molar ratio, an aqueous ammonia solution, and an aqueous base solution are mixed to form transition metal hydroxide precursor particles, which are then separated and dried, and then the transition metal hydroxide precursor particles are pulverized to have a predetermined average particle size (D50) (Step S1).
[0066] M 2 Since is a selective component, M 2 A specific description will be given below of the case where the above formula is not included.
[0067] First, a positive electrode active material precursor containing nickel (Ni), cobalt (Co) and manganese (Mn) is prepared.
[0068] In this case, the precursor for producing the positive electrode active material may be a commercially available positive electrode active material precursor, or may be produced by a method for producing a positive electrode active material precursor known in the art.
[0069] For example, the precursor may be prepared by adding an ammonium cation-containing chelating agent and a basic compound to a transition metal solution containing a nickel-containing source material, a cobalt-containing source material, and a manganese-containing source material, and then subjecting the mixture to a coprecipitation reaction.
[0070] The nickel-containing source material may be, for example, a nickel-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and specifically may be, but is not limited to, Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, fatty acid nickel salts, nickel halides, or combinations thereof.
[0071] The cobalt-containing source material may be a cobalt-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and may be, but is not limited to, Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, CoSO4, Co(SO4)2·7H2O, or a combination thereof.
[0072] The manganese-containing source material may be, for example, manganese-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, oxyhydroxide, or a combination thereof, specifically, manganese oxide such as Mn2O3, MnO2, Mn3O4, etc.; manganese salt such as MnCO3, Mn(NO3)2, MnSO4, manganese acetate, manganese dicarboxylate, manganese citrate, and manganese fatty acid salt; manganese oxyhydroxide, manganese chloride, or a combination thereof, but is not limited thereto.
[0073] The transition metal solution may be prepared by adding a nickel-containing raw material, a cobalt-containing raw material, and a manganese-containing raw material to a solvent, specifically, water or a mixed solvent of an organic solvent (e.g., alcohol, etc.) that is uniformly miscible with water, or may be prepared by mixing an aqueous solution of the nickel-containing raw material, an aqueous solution of the cobalt-containing raw material, and the manganese-containing raw material.
[0074] The ammonium cation-containing chelating agent may be, for example, NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, (NH4)2CO3, or a combination thereof, but is not limited thereto. Meanwhile, the ammonium cation-containing chelating agent may be used in the form of an aqueous solution, and the solvent used in this case may be water or a mixture of water and an organic solvent (specifically, alcohol, etc.) that is uniformly miscible with water.
[0075] The basic aqueous solution may be an aqueous solution of a basic compound, such as an alkali metal or alkaline earth metal hydroxide, a hydrate thereof, or a combination thereof, such as NaOH, KOH, or Ca(OH)2, etc. In this case, the solvent may be water or a mixture of water and an organic solvent (specifically, alcohol, etc.) that is uniformly miscible with water.
[0076] The basic compound is added to adjust the pH of the reaction solution, and may be added in an amount such that the pH of the metal solution becomes 9 to 12.
[0077] The transition metal hydroxide precursor particles may be prepared by mixing the transition metal-containing solution including nickel, cobalt, and manganese, an aqueous ammonia solution, and an aqueous base solution, and subjecting the mixture to a coprecipitation reaction.
[0078] In this case, the coprecipitation reaction can be carried out in an inert atmosphere such as nitrogen or argon at a temperature of 25°C to 60°C.
[0079] The transition metal hydroxide precursor particles produced are separated and dried in a reactor, and then pulverized to a predetermined average particle size (D50) through the process described below to form secondary particles having the desired average particle size.
[0080] Next, the pulverized transition metal hydroxide precursor particles are mixed with a lithium raw material and sintered in an oxygen atmosphere to produce secondary particles in which giant primary particles having an average particle size (D50) of 0.5 to 3 μm are aggregated (Step S2).
[0081] By producing, pulverizing and calcining the precursor particles in steps (S1) and (S2), it is possible to produce secondary particles in which large primary particles having a predetermined average particle size are aggregated.
[0082] In the step (S2), the lithium source material may be a lithium-containing sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide, or oxyhydroxide, and is not particularly limited as long as it is soluble in water. Specifically, the lithium source material may be Li2CO3, LiNO3, LiNO2, LiOH, LiOH·H2O, LiH, LiF, LiCl, LiBr, LiI, CH3COOLi, Li2O, Li2SO4, CH3COOLi, or Li3C6H5O7, and any one or a mixture of two or more of them may be used.
[0083] In the case of a high-nickel (high-Ni) NCM-based lithium transition metal composite oxide having a nickel (Ni) content of 80 mol% or more, the firing may be performed at 790 to 950°C for 5 to 35 hours in an oxygen atmosphere. In this specification, the oxygen atmosphere includes an air atmosphere and means an atmosphere containing a sufficient amount of oxygen for firing. In particular, it is preferable to perform the firing in an atmosphere having an oxygen partial pressure higher than that of the air atmosphere.
[0084] Meanwhile, the secondary small particles and secondary large particles formed by agglomeration of fine primary particles may be purchased from the market or may be directly manufactured by a known coprecipitation method. More specifically, secondary particles in which a plurality of high-content nickel-based composite transition metal hydroxide particles are assembled are generally obtained as a precursor by a coprecipitation method well known in the art, mixed with a lithium source, and then calcined. Here, the method of controlling the composition of the precursor by using the coprecipitation method, the type of the lithium source, etc. may follow common technical knowledge well known in the art.
[0085] The positive electrode active material thus prepared is used together with a conductive material and a binder to prepare a positive electrode mixture for forming a first positive electrode active material layer and a second positive electrode active material layer, and the mixture is placed on a positive electrode current collector by a conventional method to form a positive electrode active material layer, thereby manufacturing a positive electrode.
[0086] Specifically, the cathode mixture containing the cathode active material, the conductive material, and the binder is mixed in a solvent to prepare a composition for forming a first cathode active material layer, which is then coated on a cathode current collector and dried to form a first cathode active material layer. Then, the cathode mixture containing the cathode active material, the conductive material, and the binder is mixed in a solvent to prepare a composition for forming a second cathode active material layer, which is then coated on the first cathode active material layer, dried, and rolled to prepare a second cathode active material layer. The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the cathode active material, the conductive material, and the binder in consideration of the coating thickness of the slurry and the manufacturing yield, and to provide a viscosity that can achieve excellent thickness uniformity when applied for the subsequent cathode manufacturing.
[0087] Alternatively, the positive electrode may be manufactured by casting the composition for forming a positive electrode active material layer on a separate support, peeling the composition from the support, and laminating the resulting film on a positive electrode current collector.
[0088] <Lithium secondary battery> According to yet another aspect of the present invention, there is provided a lithium secondary battery including the above positive electrode.
[0089] The lithium secondary battery may further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.
[0090] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0091] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of typically 3 μm to 500 μm, and may have fine irregularities formed on the surface of the current collector to increase the adhesive strength of the negative electrode active material, as in the case of the positive electrode current collector. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.
[0092] The negative electrode active material layer may include a negative electrode active material and, optionally, a binder and a conductive material, and may be manufactured, for example, by coating a negative electrode forming composition including a negative electrode active material and, optionally, a binder and a conductive material on a negative electrode current collector and drying the composition, or by casting the negative electrode forming composition on a separate support and then peeling the composition from the support to obtain a film, which may be laminated on the negative electrode current collector.
[0093] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiOβ (0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a thin film of metallic lithium may be used as the negative electrode active material. In addition, low-crystalline carbon and high-crystalline carbon may be used as the carbonaceous material. Representative low-crystalline carbons include soft carbon and hard carbon, and representative high-crystalline carbons include amorphous, plate-like, scaly, spherical, or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, mesocarbon microbeads, mesophase pitches, and high-temperature calcined carbon such as petroleum or coal-based coke.
[0094] Additionally, the binder and conductive material are the same as those described above for the positive electrode.
[0095] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular limitation. In particular, a separator having low resistance to ion movement of the electrolyte and excellent electrolyte impregnation ability is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric material may be used to ensure heat resistance or mechanical strength, and may be selectively used in a single layer or multilayer structure.
[0096] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these.
[0097] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0098] The organic solvent may be used without any particular limitation as long as it can act as a medium through which ions involved in the electrochemical reaction of the battery can move.Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, ε-caprolactone, etc.; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; a carbonate solvent such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), or propylene carbonate (PC); an alcohol solvent such as ethyl alcohol or isopropyl alcohol; a nitrile such as R-CN (R is a hydrocarbon group having a linear, branched, or cyclic structure of C2 to C20, and may contain a double bond aromatic ring or an ether bond); an amide such as dimethylformamide; a dioxolane such as 1,3-dioxolane; or a sulfolane. Among them, carbonate-based solvents are preferable, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant capable of improving the charge / discharge performance of a battery and a low-viscosity linear carbonate-based compound (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, etc.) is more preferable. In this case, it is preferable to mix the cyclic carbonate and the linear carbonate in a volume ratio of about 1:1 to about 1:9 for excellent electrolyte performance.
[0099] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in lithium secondary batteries. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt may be within a range of 0.1 to 2.0M. If the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore exhibits excellent electrolyte performance and allows lithium ions to move effectively.
[0100] In addition to the electrolyte components described above, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving battery life characteristics, suppressing a decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5 wt % based on the total weight of the electrolyte.
[0101] The secondary battery according to the present invention is useful in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs), because the degradation phenomenon of the positive electrode material is improved.
[0102] According to yet another aspect of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.
[0103] The battery module or battery pack may be used as a power source for one or more medium to large devices including power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs); or power storage systems.
[0104] The present invention will now be described in detail with reference to exemplary embodiments so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and is not limited to the exemplary embodiments described below.
[0105] <Example 1> (Production of Positive Electrode Active Material Particles for Forming the First Positive Electrode Active Material Layer) After 4 liters of distilled water was put into a coprecipitation reactor (volume 20 L), 100 mL of 28 wt% aqueous ammonia solution was added while maintaining the temperature at 50°C. Then, a 3.2 mol / L transition metal solution, which was a mixture of NiSO4, CoSO4, and MnSO4 so that the molar ratio of nickel:cobalt:manganese was 0.8:0.1:0.1, was continuously added to the reactor at 300 mL / hr and 28 wt% aqueous ammonia solution at 42 mL / hr. The mixture was stirred at an impeller speed of 400 rpm, and a 40 wt% sodium hydroxide solution was added to maintain the pH at 9. The mixture was coprecipitation reacted for 10 hours to form precursor particles. The precursor particles were separated and washed, and then dried in an oven at 130°C to produce a precursor.
[0106] Ni synthesized by coprecipitation reaction 0.8 Co 0.1 Mn 0.1 The (OH)2 precursor was put into a mixer and crushed to a size of about 1 μm. The crushed precursor was then mixed with LiOH in a molar ratio of 1.05, and heat-treated at 800 °C for 15 hours in an oxygen atmosphere to produce LiNi 0.8 Co 0.1 Mn 0.1 O2-lithium composite transition metal oxide was prepared.
[0107] The particles obtained have an average particle size (D50) of 4 μm and are formed by agglomeration of large primary particles having an average crystal size of 250 nm and an average particle size (D50) of 2.5 μm.
[0108] (Production of Positive Electrode Active Material Particles for Forming Second Positive Electrode Active Material Layer) (Production of secondary small particles) A secondary particle in which a plurality of high-content nickel-based composite transition metal hydroxide particles are assembled is obtained as a precursor by using a coprecipitation method well known in the art, and the precursor is mixed with a lithium source and then calcined to obtain LiNi 0.8 Co 0.1 Mn 0.1 Small particles with an average particle size (D50) of 4 μm were prepared, which were made of O2 and consisted of secondary particles formed by agglomeration of fine primary particles with an average particle size (D50) of 300 nm.
[0109] (Production of secondary large particles) A secondary particle in which a plurality of high-content nickel-based composite transition metal hydroxide particles are assembled is obtained as a precursor by using a coprecipitation method well known in the art, and the precursor is mixed with a lithium source and then calcined to obtain LiNi 0.8 Co 0.1 Mn 0.1 Large particles with an average particle size (D50) of 15 μm were prepared, which were made of O2 and consisted of secondary particles formed by agglomeration of fine primary particles with an average particle size (D50) of 130 nm.
[0110] (Production of positive electrodes) 96.5 parts by weight of the positive electrode active material particles for forming the first positive electrode active material layer obtained by the above-mentioned method, 2 parts by weight of Ketjen black as a conductive material, and 1.5 parts by weight of KF9700 as a binder were dispersed in an NMP solvent to prepare a composition for forming the first positive electrode active material layer, which was then applied to an aluminum foil current collector and dried to form a first positive electrode active material layer.
[0111] Next, 97.5 parts by weight of a positive electrode active material obtained by mixing the large particles and the small particles obtained by the above-mentioned method in a weight ratio of 8:2, 1 part by weight of Ketjen Black as a conductive material, and 1.5 parts by weight of KF9700 as a binder were dispersed in an NMP solvent to prepare a composition for forming a second positive electrode active material layer, which was then applied onto the first positive electrode active material layer, dried and rolled to prepare a positive electrode.
[0112] After rolling, the first positive electrode active material layer had a thickness of 10.5 μm, and the second positive electrode active material layer had a thickness of 21 μm.
[0113] <Comparative Example 1> The same procedure as in Example 1 was carried out, except that the first positive electrode active material layer was not formed, and the second positive electrode active material layer was formed so that its thickness before rolling was the same as the total thickness of the positive electrode active material layers in Example 1.
[0114] [Experimental Example 1: Average particle size] D50 is defined as the particle size at 50% of the particle size distribution and was measured using a laser diffraction method.
[0115] [Experimental Example 2: Average crystal size of primary particles] The samples were measured using a Bruker Endeavor (CuKα, λ = 1.54 A°) equipped with a LynxEye XE-T position sensitive detector at FDS 0.5°, over the 2θ range of 15° to 90° with a step size of 0.02° for a total scan time of 20 min.
[0116] The measured data were subjected to Rietveld refinement, taking into account the charge (+3 for metals at transition metal sites, +2 for Ni at Li sites) and cation mixing from each site. For crystal size analysis, instrumental broadening was considered using the Fundamental Parameter Approach (FPA) implemented in the TOPAS program made by Bruker, and the entire peak in the measurement range was used for fitting. Peak morphology was fitted using only the Lorenzian contribution in the First Principle (FP) of the peak types available in TOPAS, and strain was not considered at this time.
[0117] Using the positive electrodes of the Examples and Comparative Examples prepared by the above-mentioned methods, lithium secondary batteries were prepared as follows.
[0118] A 5:5 mixture of artificial graphite and natural graphite was used as the negative electrode active material, and Super P was used as the conductive material, and SBR / CMC was used as the binder in a weight ratio of 96:1:3 to prepare anode slurry. The slurry was then applied to one side of a copper current collector, dried and rolled to manufacture the anode.
[0119] A porous polyethylene separator was interposed between the positive and negative electrodes prepared as above to prepare an electrode assembly. The electrode assembly was then placed inside a case, and an electrolyte was then injected into the case to prepare a full cell lithium secondary battery.
[0120] The electrolyte was prepared by dissolving lithium hexafluorophosphate (LiPF6) at a concentration of 1.0 M in an organic solvent consisting of ethylene carbonate / ethyl methyl carbonate / diethyl carbonate (EC / EMC / DEC mixed volume ratio = 3 / 4 / 3).
[0121] [Experimental Example 3: Measurement of short circuit occurrence according to roll press pressure during electrode rolling] The positive electrodes of the Examples and Comparative Examples were rolled using a roll press, and the change in porosity and the occurrence of short circuits according to the pressure were measured. The results are shown in Table 1 below.
[0122] [Table 1]
[0123] [Experimental Example 4: Measurement of life characteristics and resistance increase rate] For the full cells of the lithium secondary batteries manufactured according to the examples and comparative examples, the capacity retention rate and the resistance increase rate after 400 cycles were measured by the following method.
[0124] The manufactured lithium secondary battery full cell was charged at 0.5 C to 4.2 V in CC (constant current)-CV (constant voltage) mode at 45° C., and discharged at a constant current of 1 C to 2.5 V, and then a charge-discharge experiment was performed 900 times to measure the capacity retention rate and the resistance increase rate. The results are shown in FIG. 3 and Table 2.
[0125] [Table 2]
Claims
1. A current collector; A first positive electrode active material layer formed on at least one surface of the current collector, The cathode active material particles include at least one type of particle selected from the group consisting of large primary particles having an average particle size (D50) of 0.5 to 3 μm, secondary particles having an average particle size (D50) of 3 to 7 μm formed by agglomeration of the large primary particles, and a mixture of these particles; a first positive electrode active material layer, the first positive electrode active material layer having a mean crystal size of 200 nm or more; A second positive electrode active material layer formed on the first positive electrode active material layer, Positive electrode active material particles formed by agglomerating large primary particles having an average particle size (D50) of 0.5 to 3 μm, or formed by agglomerating fine primary particles having an average particle size (D50) smaller than that of the large primary particles, and consisting of secondary small particles having an average particle size (D50) of 1 to 7 μm; a second positive electrode active material layer including positive electrode active material particles composed of secondary large particles having an average particle size (D50) of 7 to 20 μm formed by agglomeration of the fine primary particles having an average particle size (D50) larger than that of the secondary small particles and smaller than that of the giant primary particles; the positive electrode active material particles are a positive electrode active material made of a nickel-based lithium transition metal oxide, The content of the secondary small particles is 10 to 100 parts by weight based on 100 parts by weight of the secondary large particles.
2. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the fine primary particles have an average particle size (D50) of 100 to 900 nm.
3. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the fine primary particles have an average particle size (D50) of 100 to 400 nm.
4. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the first positive electrode active material layer and the second positive electrode active material layer each have an average particle size (D50) of 1 to 3 μm.
5. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the average particle size (D50) of the secondary small particles is 2 to 5 μm, and the average particle size (D50) of the secondary large particles is 8 to 16 μm.
6. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the average particle size (D50) of the secondary large particles:the average particle size (D50) of the secondary small particles is 5:1 to 2:
1.
7. The thickness (a) of the second positive electrode active material layer and the thickness (b) of the first positive electrode active material layer satisfy the following formula 1: [Formula 1] 3b≦a The positive electrode for a lithium secondary battery according to claim 1 .
8. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the secondary small particles consist solely of secondary small particles formed by agglomeration of the fine primary particles.
9. The nickel-based lithium transition metal oxide is Li a Ni 1-x-y Co x M 1 y M 2 w O 2 (1.0≦a≦1.5, 0≦x≦0.2, 0≦y≦0.2, 0≦w≦0.1, 0≦x+y≦0.2, M 1 is one or more metals selected from Mn and Al; M 2 2. The positive electrode for a lithium secondary battery according to claim 1, wherein R is one or more metal elements selected from the group consisting of Ba, Ca, Zr, Ti, Mg, Ta, Nb and Mo.
10. The nickel-based lithium transition metal oxide is Li a Ni 1-x-y Co x Mn y O 2 10. The positive electrode for a lithium secondary battery according to claim 9, wherein a is an integer of 1.0≦a≦1.5, 0≦x≦0.2, 0≦y≦0.2, and 0≦x+y≦0.
2.
11. A lithium secondary battery comprising the positive electrode according to any one of claims 1 to 10.
Citation Information
Patent Citations
Electrode for battery
JP2006210003A
Lithium secondary battery positive electrode and lithium secondary battery including the same
JP2013211096A
Positive electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2019029205A
Cathode material, cathode, and lithium secondary battery containing lithium manganese-based cathode active material with spinel structure
JP2020532842A
Positive electrod for secondary battery having the second-layered structure comprising electrode active material having different property in each layer
KR1020210063029A